Rancangan Kurikulum “Penuh Kasih” di Kaum Wanita Gereja Beth-El Tabernakel Kristus Alfa Omega Tirtoyoso - zalukhu, Auguslinia; Franspebri, Yoel; Suraswati, Febe (STT Kristus Alfa Omega, 2025)
Gereja Beth-El Tabernakel Kristus Alfa Omega Tirtoyoso, due to the presumed unavailability of a curriculum, only has a general theme prepared by the church leaders, while the specific themes for each meeting are individually prepared by the serving ministers. Based on this problem, the research question is formulated as follows: How appropriate is the “Penuh Kasih” (Full of Love) curriculum design for the women's ministry at Gereja Beth-El Tabernakel Kristus Alfa Omega Tirtoyoso. Therefore, this study aims to evaluate the appropriateness of the “Penuh Kasih” curriculum design for the women’s ministry at Gereja Beth-El Tabernakel Kristus Alfa Omega Tirtoyoso. This research employs a mixed-methods approach using a sequential explanatory model, combining both quantitative and qualitative data. The type of research used is Level 1 Research and Development (R&D), aiming to produce a curriculum design as the final product. The result of this study is the “Penuh Kasih” curriculum design, which was quantitatively assessed by 20 experts with excellent results and qualitatively reviewed through interviews with 10 experts. The experts concluded that the curriculum is well-structured and relevant.